IMPLIKASI COVID -19 TERHADAP KESADARAN HUKUM BERLALU LINTAS DI KABUPATEN INDRAGIRI HILIR - Fitri Wahyuni, Indra Muchlis, Syarifuddin (Fakultas Hukum Universitas Komputer Indonesia, 2021)
COVID-19 as a global pandemic has significance for various aspects of the life of society, nation and state. Of the various aspects affected, one of which is the legal aspect, especially related to the awareness of traffic laws during the Covid 19 period. In this study the main problems are (1) What are the implications of Covid-19 on traffic law awareness in Indragiri Hilir Regency (2) ) What efforts did the police make to overcome the low level of legal awareness during the Covid-19 period in Indragiri Hilir Regency. This research is a sociological legal research that examines the applicable legal provisions and what happens in reality in society. Data collection techniques are through field observations and interviews with respondents. The occurrence of covid 19 had an impact on the awareness of traffic laws in Indragi Hilir Regency. This is evident from the results of research conducted by field researchers that there were many traffic violations during the Covid 19 period because the motorcycle riders thought that there was tolerance from law enforcement officers in making repressive efforts (prosecution) for those who violated traffic rules. During the Covid 19 era, people paid more attention to health protocols than road traffic rules, such as they were more afraid of not wearing masks than not wearing helmets on the road while driving a motorcycle. This assumption clearly shows that the level of legal awareness in road traffic is still low. Efforts are made to increase legal awareness through prevention and enforcement efforts. Prevention efforts are more advanced than prosecution during the Covid 19 period